Oxford, Bodleian Library, Trinity College MS 93: a study and partial edition - Schuhle-Lewis, H (2019)
This thesis examines the Middle English Declaracion on the Bible contained uniquely in Oxford, Bodleian Library, Trinity College MS 93. The text represents a fascinating and methodologically varied response to the Later Version of the Wycliffite Bible (LV), written very soon after its completion.